2002
DOI: 10.1046/j.1365-2125.2002.01581.x
|View full text |Cite
|
Sign up to set email alerts
|

Population pharmacokinetics model and limited sampling strategy for intravenous vinorelbine derived from phase I clinical trials

Abstract: Aims a) To characterize the pharmacokinetics of intravenous vinorelbine, b) to use a population analysis for the identification of patient covariates that might appreciably influence its disposition and c) to define a limited sampling strategy for further Bayesian estimation of individual pharmacokinetic parameters. Methods All data were collected from 64 patients (99 courses) entered in three different phase I trials that have been previously reported. All patients received vinorelbine as a 20 min infusion wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 21 publications
3
31
0
Order By: Relevance
“…Moreover, a significantly decreased vinorelbine plasma clearance was reported when docetaxel infusion was immediately followed by a 10-min intravenous vinorelbine bolus in comparison with the inverse sequence (106 and 216 l/h, respectively) [14]. However, mean values of both vinorelbine blood clearance and docetaxel plasma clearance were consistent with those previously reported for single-agent chemotherapy (39.4 [9] and 36.8 l/h [10], respectively). Then, pharmacokinetic interaction was not likely to occur in this schedule.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Moreover, a significantly decreased vinorelbine plasma clearance was reported when docetaxel infusion was immediately followed by a 10-min intravenous vinorelbine bolus in comparison with the inverse sequence (106 and 216 l/h, respectively) [14]. However, mean values of both vinorelbine blood clearance and docetaxel plasma clearance were consistent with those previously reported for single-agent chemotherapy (39.4 [9] and 36.8 l/h [10], respectively). Then, pharmacokinetic interaction was not likely to occur in this schedule.…”
Section: Discussionsupporting
confidence: 79%
“…The mean docetaxel and vinorelbine clearance (i.e. 24.5 and 23.8 l/h/m 2 , respectively) are similar to previously reported values [10, 11]. Of note, the patient who had fever in cycle 1 (i.e.…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Intravenous vinorelbine has been approved and marketed in many countries since 1989 for non-small-cell lung cancer and advanced breast cancer. To identify the main sources of variability in vinorelbine after IV administration a previous population PK analysis was carried out in 64 phase I patients (n=99 PK data sets) [6]. An interpatient variability of 30% (expressed in CV) and intrapatient variability of 10% in total clearance were determined.…”
Section: Introductionmentioning
confidence: 99%
“…Oral vinorelbine is effective in NSCLC but exerts slightly higher gastrointestinal toxicity. Crossover studies assessing the bioavailability of oral and intravenous vinorelbine [19] showed that an oral dose of 80 mg/m 2 resulted in similar exposure as the intravenous dose of 30 mg/m 2 and that the oral dose of 60 mg/m 2 is comparable to the intravenous dose of 25 mg/m 2 which is the dose commonly used in combination regimens [20]. Therefore, we decided to define the highest level in this phase I trial as a dose of oral vinorelbine of 60 mg/m 2 and to initiate the trial with a lower dose of 40 mg/m 2 corresponding to approximately to 15 mg/m 2 of intravenous vinorelbine and escalate the dose over a total of 3 levels.…”
Section: Discussionmentioning
confidence: 99%